METODE DIALEKTIKA HEGEL DAN ANALISISNYA ATAS PARADIGMA HUKUM - Muhammad Zulfikar Nur Falah; Ari Bachtiar Firmansyah; Luqman Hakim (Sekolah Tinggi Agama Islam Sadra, 2022)
This article talks about the analysis of Hegel's dialectical method on the law paradigm, which, as is well known, the problem with the development of legal science, has recently only been viewed from a certain point of view, so that it is not as detailed as possible to provide an open solution. On the factor of the law paradigm that has been used, the author then makes a special research object to be investigated using descriptive analysis methods obtained through library research, with relevant and reliable sources such as books, journals, theses, theses, dissertations, and so on. Before obtaining an understanding of the implications of this research, the author first describes the biography of Hegel, and his dialectical method. Implicitly, this is so reflective, because it is able to reveal and produce the truth behind the nature of knowledge contained in the field of philosophy or the historical reality of the law paradigm. The dialectical series consists of the postmodernism law paradigm, which is the